2023
DOI: 10.3389/fpsyg.2023.1298485
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child attachment and mental health in young adolescents: a moderated mediation analysis

Rong Tan,
Yizhi Yang,
Tao Huang
et al.

Abstract: IntroductionThe parent–child attachment has a significant impact on adolescents’ mental health. However, the influence of psychological quality and coping styles on this connection remains unknown. This study examined the relationship between parent–child attachment and adolescent mental health, by exploring the mediating role of psychological quality and the moderating role of coping styles.MethodsA total of 633 young adolescents participated in this study after signing informed consent. They anonymously comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…The reason may be that the sampling grade is freshman year, and the differences in different majors have not yet been shown. The development of positive mental characters among only child students is better than that of non only child students, possibly due to the superior educational environment of only child families, which can receive more attention and emotional satisfaction from parents 15 . The development of positive mental characters among students born in urban areas is better than that of students born in rural areas.…”
Section: Discussionmentioning
confidence: 98%
“…The reason may be that the sampling grade is freshman year, and the differences in different majors have not yet been shown. The development of positive mental characters among only child students is better than that of non only child students, possibly due to the superior educational environment of only child families, which can receive more attention and emotional satisfaction from parents 15 . The development of positive mental characters among students born in urban areas is better than that of students born in rural areas.…”
Section: Discussionmentioning
confidence: 98%
“…Along similar lines, parental attachment is one of the most important aspects of a child's life. The researches have concluded that a strong parent-child bond can control psychiatric illness [10][11][12][13][14][15]. Beginning in the neo-natal stages and continuing throughout the life of a child, the parental attachment is deemed to be important while studying depression among students.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with high-quality parent-child attachment have been shown to have better mental health outcomes, whereas those with low-quality attachment were more likely to internalize psychological disorders and externalize behavioral problems [12,13]. Another study involving 633 early adolescents found that the psychological quality partially moderated the association between parent-child attachment and adolescents' mental health, and that parentchild attachment significantly and positively predicted adolescents' mental health [14]. Many studies have focused on parental attachment and the course of development of depressive symptoms among adolescents [15].…”
Section: Introductionmentioning
confidence: 99%